Photovoltaic Characterization of Si and SiGe Surfaces Sonochemically Treated in Dichloromethane - Shmid, V.; Podolian, A.; Nadtochiy, A.; Yazykov, D.; Semenko, M.; Korotchenkov, O. (Journal of Nano- and Electronic Physics, 2020)
It is well known that the near-surface recombination and trapping of photoexcited free carriers significantly affect the photovoltaic performance. Passivation techniques are therefore in great demand for current photovoltaic technologies. Different aspects of the surface passivation in Si and SiGe were widely addressed. It was particularly concluded that sonochemical surface treatments, e.g. in chloroform (CHCl3), can significantly improve the photovoltaic response. It is shown in this work that another reactive surface etchant containing carbon, dichloromethane (CH2Cl2), placed into the sonochemical reactor can effectively modify the surface photovoltaic response of Si and SiGe surfaces. X-ray diffraction studies revealed that the Si-Ge alloy layer exhibits solid solutions of Si in Ge (approximately 59 % of Si atoms) and Ge in Si (approximately 90 % of Si atoms). An order of magnitude larger photovoltaic signal, which is accompanied by slightly prolonged decay times, is observed in single crystal Si. A 50 % increase in the photovoltaic amplitude is reproduced in SiGe. In contrast to Si, sonochemical treatment of the SiGe surface tends to speed up the short-term component and slow down the long-term component of the double-exponential surface photovoltage signal. As dichloromethane acts as a carbon source, it can be suggested that sonochemically decomposed carbon atoms can effectively passivate silicon dangling bonds. We believe this sonochemical treatment step can be used for the surface passivation in manufacturing Si- and SiGe-based solar cells.